Crack-tip plasticity and intrinsic toughening in nano-sized brittle amorphous carbon. (April 2020) - Shin, Dahye; Jang, Dongchan
Abstract: Most monolithic brittle materials are vulnerable to the failure by cracks because of a lack of intrinsic toughening mechanisms, such as the plasticity in the vicinity of the crack front. As a result, most of the efforts to mitigate the sudden failure of brittle ceramics have been focused on developing the extrinsic toughening mechanisms that hinder crack propagation behind the tip, such as the fiber bridging. In this work, we experimentally demonstrate that the intrinsic toughening arises even in the brittle monolithic ceramic material such as diamond-like carbon (DLC) when its external dimension reduces down to sub-micron scales. This unique phenomenon owes its origin to the decrease of the crack driving force in the small samples, which in turn enables them to bear high enough stresses to activate the local atomic plasticity. Through nanomechanical tensile and bending experiments, electron energy loss spectroscopy analysis, and finite element method for stress distribution calculation, we confirmed that the local atomic plasticity associated with sp 3 to sp 2 rehybridization is responsible for the intrinsic toughening. Highlights: Mode I fracture toughness of nano-sized diamond-like carbon is measured by tensile experiments on the samples three different notch and specimen geometries. High shear stress fields near the crack tip of nano-sized DLC causes the local plasticity and consequently enhances the fracture toughness. The enhancement of the fracture toughness is attributed to the atomic scale plastic deformation associated with the shear-stress driven sp 3 to sp 2 bond transition.